The Use of Botulinum Toxin in Complex Hernia Surgery: Achieving a Sense of Closure - Whitehead-Clarke, Thomas; Windsor, Alastair (Frontiers in Surgery, 2021)
Abdominal wall surgeons have developed a host of tools to help facilitate fascial closure. Botulinum toxin A is one of the most recently identified treatments and has grown in popularity over recent years; showing great promise in a number of case series and cohort studies. The toxin paralyses lateral abdominal wall muscles in order to increase laxity of the tissues – facilitating medialisation of the rectus muscles. Several research groups around the world are developing expertise with its use- uncovering its potential. We present a review of the relevant literature over the last two decades, summarizing the key evidence behind its indications, dosing and effects.